2013
DOI: 10.1097/iop.0b013e31827a7622
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of 2,480 Space-Occupying Lesions of the Orbit From 1976 to 2011

Abstract: The authors' findings highlight the distinctive nature of the orbital oncology experience at an ocular oncology department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
1
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(159 citation statements)
references
References 26 publications
6
133
1
12
Order By: Relevance
“…[3][4][5][6][7][8][9][10] Bonavolontà et al 3 observed that dermoid cyst (14%) was the most common orbital disease noted in their study. On the other hand, Shields et al 6 and Jamison et al 10 reported idiopathic orbital inflammation and lymphoproliferative tumour as the two most common orbital diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] Bonavolontà et al 3 observed that dermoid cyst (14%) was the most common orbital disease noted in their study. On the other hand, Shields et al 6 and Jamison et al 10 reported idiopathic orbital inflammation and lymphoproliferative tumour as the two most common orbital diseases.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The heterogeneity of orbital diseases frequently poses a diagnostic dilemma to the attending clinicians. [3][4][5][6][7][8][9] When diagnosis cannot be made confidently on the ground of clinical and radiological findings, orbital biopsy is required to help achieve the definitive diagnosis before an appropriate management plan is formulated.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of our patients were the same as in the literature. There was no difference with the current literature (1,20 (18) used a CT-and MRI-based navigation system in 10 patients who had orbital tumors. They emphasized the importance of this system on the orbital surgery.…”
Section: Bonavolonta Et Almentioning
confidence: 70%
“…It is classified by the International Society for the Study of Vascular Anomalies as a low-flow vascular malformation 1 . It occurs in 4% of all orbital lesions and 25% of the vascular lesions 2,3 .…”
Section: Introductionmentioning
confidence: 99%